Failure modes of CFRP flexural strengthened steel I-beams - Narmashiri, K.; Jumaat, Mohd Zamin; Sulong, N.H.R. (2011)
This paper presents the experimental and numerical studies on the flexural strengthened steel I-beams by using Carbon Fiber Reinforced Polymer (CFRP) strips. Nowadays, strengthening existing steel structures by using CFRP has been widely interested. One of the common usages of CFRP to strengthen steel beams is the flexural upgrading. In this case, CFRP strips are pasted on the tensile flange to improve flexural behaviors. The problems that are frequently reported for CFRP strengthened steel beams are the debonding, delaminating (peeling), and splitting. Identification these failure modes are essential to provide an appropriate level of safety for strengthened steel beams. To investigate the CFRP failure modes, four strengthened steel I-beams were chosen. The CFRP plates with different thicknesses in single and double (splice) layers were used. Both experimental test (four-points bending test) and numerical simulation (full 3D simulation with ANSYS) were employed. The incremental loading was applied until failure while deformations in the critical regions were recorded. The results reveal that for the CFRP flexural strengthened steel beams the following failure modes occurred: (a) debonding at the CFRP plate tips, (b) debonding below point loads, (c) delaminating at the ends of CFRP plate, and (d) splitting below point loads. The sequence of failure modes depended on the specifications of CFRP plate. Some recommendations are provided to overcome/retard these failures.